Evaluation of complications of conventional frenulopasty and z-plasty technique: Evaluasi komplikasi frenulopasti teknik konvensional dan teknik z-plasty - Basyar, Husnul (Makassar Dental Journal, 2025)
Although complications of ankyloglossia management are very low, bleeding, recurrence, lip injury, Wharton's duct injury, infection, lingual dysfunction, weight loss, pain and airway compromise may occur; recurrence being the highest. This article discusses the complications of conventional frenuloplasty technique and z-plasty technique in ankyloglossia cases in Makassar from January 2019 to March 2022. A total of 21 children aged 7 months to 10 years had ankyloglossia, 17 cases were treated with z-plasty technique and 4 cases with conventional technique. Haemorrhage occurred in 1 patient of z-plasty technique and recurrence oc-curred in 2 conventional techniques. It was concluded that conventional frenuloplasty technique more often caused recurrence complications. The z-plasty technique frenuloplasty did not show recurrence but due to aggressive tissue release it may cause bleeding although the incidence rate is very low.